Metode Pendidikan Sebaya dan Metode Ceramah dalam Meningkatkan Pengetahuan Siswa tentang HIV/Aids - Komang Ayu Henny Achjar (Jurnal Gema Keperawatan, 2013)
The aim of this study is to find out of the effectiveness of peer education method with lecture method in improve the junior high school students knowledge about HIV/AIDS. This type of research was Quasy experiment with non equivalent control group design with pre post test. Peer education methods have been implementation in SMP 1 Blahbatuh as experiment group and lecture methods in SMPN 2 Blahbatuh as control group, contain each group 40 sample. The results showed the mean peer education methods group was 58 (pre) and 81,25 (post), and the mean on the lecture methods group was 57,87 (pre) and 65,62 (post). The result of analysis with Mann Whitney test have been obtained p value 0,000, its mean that peer education methods was more effective than the lecture methods in improve the junior high school students knowledge about HIV/AIDS.